Specific features of team kinds of sports sportsmen’s individual characteristics - V.N. Liashenko; V.N. Tumanova; E. V. Hatsko; Y.N. Korzh (Physical Education of Students, 2016)
Purpose: to study individual characteristics of personalities of team kinds of sports sportsmen, specializing in football. Material: in the research football players (n=28, age 18 - 20 years) participated. Psycho-diagnostic testing by methodic 16PF of Kattel was used. Results: we found high correlation between factors, which were conditioned by caution in choosing partners for communication and active contacts. Such sportsmen express their emotions expressively. It facilitates improvement of relations in conditions of co-operation in little group. It was also found that one of personality’s leading characteristics in sportsmen is their activity in social contacts. The higher is courage the more active is communication. It promotes discussion of common interests and targets for the given group of people. Conclusions: Sportsmen, who have many emotional interests and are ready to risk (or having bent to adventures) have to face non understanding of other players. In such case conflict can be inevitable. Especially it manifests, if opposite side has the same indicators in this factor. Just courage, risk and adventurism push them to conflict solution of problem situations.